Pediatric Cardiac Service Development Programs for Low- and Middle-Income Countries in Need of Improving or Initiating Local Services - Novick, William M.; Molloy, Frank; Bowtell, Karen; Forsberg, Brian; Pavanić, Martina; Polivenok, Igor; Rao, Sri; Muñoz, Yamile; Cardarelli, Marcelo (Frontiers in Pediatrics, 2019)
Pediatric cardiac services are deficient in most of the world. Various estimates are that between 80-90% of the world’s children do not receive adequate cardiac care for their congenital or acquired heart disease. We began a modest effort in 1992 to assist in the development of pediatric cardiac services in low- and middle-Income countries (LMIC). Since then, we have provided services in 32 countries based on 3 distinctive development strategies, in order to meet the local needs for pediatric cardiac services. Our goal has always been to provide education, training and sufficient experience so that eventually we leave a site with a fully functional, independently operating pediatric cardiac service that is sustainable over time. The margin between success and failure is dependent upon a number of factors and we hope that this chapter will provide others with the tools for success.